LEGAL REGULATION OF MEASURES OF STATE SUPPORT IN THE PROCESS OF THE IMPLEMENTATION OF NORTHERN DELIVERY - Galina V. Goncharuk, (Russian Studies in Law and Politics)
The relevance of the issue investigated in the article lies in the need to provide state support measures for the implementation of northern delivery measures to the territory of the Arctic zone of the Russian Federation in order to ensure the preservation of human capital here.